Risk of consecutive immunogenic failure in switchers of anti-tumor necrosis factor alpha among patients with inflammatory bowel diseases. (January 2022) - Yanai, Henit; Ungar, Bella; Kopylov, Uri; Fischler, Tali Sharar; Biron, Irit Avni; Ollech, Jacob E.; Goren, Idan; Matar, Manar; Perets, Tsachi Tsadok; Shamir, Raanan; Dotan, Iris; Amir, Shira; et al.
Background: Evidence regarding the risk of immunogenicity in patients with inflammatory bowel disease (IBD) who switched anti-tumor necrosis factor alpha (anti-TNFα) therapies to a subsequent anti-TNFα (either infliximab or adalimumab) is conflicting. We aimed to assess the risk of consecutive immunogenicity to anti-TNFα in a large cohort of patients. Methods: This was a multicenter retrospective study. Medical records of adult and pediatric IBD switchers who had pharmacokinetic data for both agents between 2014 and 2020 were retrieved. Data including age, sex, disease type, duration of therapies, and concomitant use of immunomodulators (IMMs) were recorded. Results: Overall, 164 patients were included [52% female; 88% Crohn's disease; mean age = 24.4 ± 14.6 years; 108 (66%) switched from infliximab to adalimumab and 56 (34%) vice versa]; 120 (73.1%) patients switched due to an immunogenic failure. Among patients switching therapy from infliximab to adalimumab due to an immunogenic failure immunogenicity to infliximab was significantly associated with consecutive immunogenicity to adalimumab ( p = 0.026). Forthy four out of 120 patients (36.6%) with an immunogenic failure to the first anti-TNFα started an IMM with the second anti-TNFα. This combination with IMM was not associated with reduction of consecutive immunogenicity ( p = 0.31), but it was associated with longer drug retention ( p = 0.007). Multivariate analysis demonstrated that older age at second anti-TNFα, adjusted to the chronology of therapy and sex, was associated with increased immunogenicity to the second anti-TNFα. Conclusion: Patients with IBD who switch from infliximab to adalimumab following an immunogenic failure are at increased risk for consecutive immunogenicity to adalimumab. IMM use after a switch prolongs drug retention.